Application of different Nanocatalysts in industrial effluent treatment: A review - Eskandarinezhad, Sara; Khosravi, Reza; Amarzadeh, Mohamadamin; Mondal, Piyal; Magalhães Filho, Fernando Jorge Correa (Journal of Composites and Compounds, 2021)
The manufacturing, application, and design of chemical processes and products that minimize or remove waste and the use of dangerous and toxic reagents are referred to as green chemistry. Green chemistry is made up of twelve principles, one of which is catalysis. The role of catalysis is to accelerate the reaction by introducing a substance called a catalyst. Because of their high efficiency, productivity, activity, and selectivity, nanocatalysts have recently received many interests. Nanocatalysts are characterized by their high surface area to volume ratio, as well as their nanoscale forms and sizes. One of the significant applications of nanocatalysts is wastewater and wastewater purification. Green and bio-synthesized nanocatalysts could be used efficiently to remove heavy metals, medicinal, organic, and inorganic pollutants from the wastewater systems. This paper reviews nanocatalysts based on noble and magnetic nanocatalysts, as well as metal catalysts supported by organic polymers, and discusses their industrial effluent treatment mechanisms.